Microbiology Plate Rounds: Bridging the Gap between Didactic Coursework and Real-World Application...American Society for Clinical Laboratory Science (ASCLS) Clinical Laboratory Educators’ Conference February 19-21, 2015 in Cincinnati, Ohio - Webb, Tera L. (Clinical Laboratory Science)
Plate rounds can be a means to effectively bridge the gap between didactic coursework and real-world application. At the University of Alabama at Birmingham, the Clinical Laboratory Sciences program has implemented plate rounds into the Clinical Microbiology curriculum. The focus is not on just bacteria identification but also on antibiotic susceptibility patterns, clinical correlation, reporting guidelines, and consulting. During plate rounds, each of six stations were set-up to include a case, a microbial culture, a microscope with unknown slide, and a Mueller-Hinton with susceptibility or Microscan panel. Each station had rapid tests and, for reference, a Clinical Microbiology Standard Operating Procedure Manual. This manual is a reproduction of a hospital clinical microbiology manual which contains algorithms, testing procedures, work-up procedures, susceptibility testing guidelines, and reporting guidelines. Students were required to effectively correlate the cases with their findings, notate what would be released to the patients chart, and answer questions that would enhance their ability to consult on each specific case. One hundred percent of the students surveyed agreed that the activity helped them with their didactic coursework, their ability to correlate pathological manifestations with significant isolates, and it increased their interest in the application of microbiology in the clinical laboratory. Through simulation, students gained an understanding of how didactic coursework is applied in a hospital clinical microbiology laboratory.